Teknik WDEP Dalam Meningkatkan Keterampilan Belajar Siswa - Mutiara Salsabila; Yenti Arsini; Mahyuni Harahap (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2024)
Learning skills are the skills to manage one's potential in carrying out daily activities (learning) which are influenced by several factors that produce changes to achieve goals. Hopefully, using the WDEP technique as part of the reality of counseling can change learning skills for the better. The aim of this research is to improve students' learning skills. This research uses qualitative methods and action research (action research). Through the use of the WDEP technique, students are able to help themselves face reality and fulfill basic needs without harming themselves or others, students are able to have greater control over their own lives and are able to make better choices in improving their learning skills and are committed to responsible for the plans he has made.